Yard, Joey. Skates and picture of Pope John Paul II in shed. - Tennier-Stuart, Emma (2014)
Detail of one wall of Joey Yard's shed, with hockey skates, a photo of Pope John Paul II, landscape photos, and wall writing ("1995 COD WAR BETWEEN SPAIN + CANADA")